Job satisfaction and work context among rehabilitation care professionals in Alagoas, Brazil: an observational study - Mônica Thalia Brito de Melo; Carlos Dornels Freire de Souza; Katia Suely Queiroz Silva Ribeiro; Jussara Almeida de Oliveira Baggio (Universidade de São Paulo, 2023)
ABSTRACT Job satisfaction is multifactorial and is directly related to the quality of health services. The main objective of this study was to characterize the level of job satisfaction and the work context of the multidisciplinary teams in specialized rehabilitation services in the state of Alagoas, Brazil. We evaluated the professional profile of participants and sociodemographic information. The Work Context Assessment Scale (WCAS) which is divided into three dimensions and questions adapted from the satisfaction and remuneration dimensions of the Great Place to Work methodology for the Organizational Climate Survey, was used. We included 190 professionals, the mean age was 35.47±9.25 and 86.3% were women. Most participants worked in the capital (60%) and 84.7% had a monthly wage ranging from R$1,000 to R$3,000. The dimension of "work organization" was crucial. The items "pace of work," "strong demand," "performance monitoring," and "repetitive tasks" presented the worst results, but 92.7% are satisfied with their professional activities. The logistic regression analysis showed that more years since graduation and lower scores of Work conditions and Socio-professional relationships were associated with higher job satisfaction. Job satisfaction was found to be high, the dimension of work organization was crucial, and almost half of the participants have already thought about leaving their careers.